EFFECTS FROM THE JUNE 10, 2021 SOLAR ECLIPSE IN THE HIGH-LATITUDE IONOSPHERE: RESULTS OF GPS OBSERVATIONS - Chernogor, L.; Mylovanov, Yu; Luo, Y. (Radio physics and radio astronomy (Print), 2022)
Subject and Purpose. The unique natural phenomena which solar eclipses are can activate coupling between the subsystems of the Earth–atmosphere–ionosphere–magnetosphere system. Following an eclipse, disturbances may get induced in all the subsystems and their associated geophysical fields. It is important that a subsystem’s response does not depend on the phase of the eclipse alone, but also on the state of space weather and the observation site coordinates. The majority of solar eclipses occur at middle and low latitudes. The maximum phase of the June 10, 2021 annular eclipse was observed at high latitudes, including the North Pole. The highlatitude ionosphere is fundamentally different from the mid- and low-latitude ionosphere as it stays in a metastable state, such that any impact may be capable of activating subsystem coupling. The relevance of this study is conditioned by the diversity of the solar eclipse effects in the high-latitude ionosphere. The purpose of this work is to present observational results concerning variations in the total electron content (TEC) in the high-latitude ionosphere in the course of the June 10, 2021 solar eclipse. Methods and Methodology. An array of eleven terrestrial GPS receive stations and eight GPS satellites were used for the observations. Results. The effects from the solar eclipse were distinctly observable at all eleven reception sites and from all the eight satellites. On the average, i.e. with random fluctuations neglected, changes in illumination at ionospheric heights were followed by decreases in the TEC. All of the observation records demonstrated a decrease in the TEC at the early stage of the eclipse. Some 60 to 100 min later the TEC attained a minimum and then returned to virtually the initial value. The lowest observed magnitude of the TEC was 1.0–5.1 TEC units, while, on the average, it was found to be 2.7 ± 1.6 TEC units, or 35 ± 18%. The greatest decrease in the TEC lagged behind the maximum phase of the solar eclipse (lowest illumination at the heights of the ionosphere) by 5–30 min, or 15.7 ± 6.8 min on the average. A few TEC records obtained at different stations showed quasi-periodic variations with the periods ranging from 5 to 19 min and amplitudes of 1 to 12%. Conclusions. The annular eclipse of June 10, 2021 acted to significantly disturb the high-latitude ionosphere where aperiodic and quasi-periodic disturbances of the TEC took place.